Application of Differential Equation in the Design of Dialysis Machine - Timsina, Ramesh Chandra (Patan Gyansagar, 2024)
In this work, I have discussed the application of differential equations in the design of a dialyzer machine. A dialyzer is a device through which blood flows from the patient's body into the machine. A substance called dialysate flows through the machine in the opposite direction to the blood. This aids in separating waste materials with the help of a semipermeable membrane attached to the machine. This membrane possesses minute pores that allow the passage of waste matter, which has much smaller molecules than the blood cells, but restrict the passage of blood itself. The design of the dialyzer machine concerns the flow rate of the waste material through the membrane. This flow-rate is determined by the differences in concentration of waste material on either side of the membrane, where, the flow occurs from high concentration to low concentration.